Treatment outcomes of ABVD in classical Hodgkin lymphoma patients from Thailand without procarbazine access - Suprang Suttantapidok; Smith Kungwankiattichai; Weerapat Owattanapanich (Scientific Reports)
Abstract Classical Hodgkin lymphoma (cHL) is a highly-curable, aggressive form of lymphoma with disparities between international guidelines and treatment in resource-limited countries. We aimed to report outcomes in a multi-centered retrospective cohort of all cHL patients ≥ 18 years old exclusively treated with ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) without positron emission tomograph (PET)-adapted treatment between 2013 and 2022 in Thailand. First-line core treatment goals (FL-CTGs) for a resource-limited middle-income country were also investigated. One hundred ninety-two patients were included (median age 28.0 years, range 15, 79). The patients had an objective response rate of 90%. The 3-year overall survival (OS) was 94.6% (95%CI 89.8%, 97.2%), and the 3-year progression-free survival (PFS) was 62.2% (95%CI 54.2%, 69.3%). Both 3-year OS and PFS rates were higher in patients achieving FL-CTGs compared with those not achieving them in the early stage (Ann Arbor stages I and II) and advanced stage (Ann Arbor stages III and IV) groups. Advanced-stage patients not achieving FL-CTGs had a significantly higher risk of progression, relapse, or all-cause mortality (aHR 3.77, 95%CI 1.74, 8.17; p < 0.001). In conclusion, cHL patients treated exclusively with ABVD without PET-adapted treatment had good survival outcomes and achieving FL-CTGs is essential for good survival outcomes.